2020
DOI: 10.1111/jocs.15162
|View full text |Cite
|
Sign up to set email alerts
|

Decision analysis and personalized clinical tool for cerebrospinal fluid drains in thoracoabdominal aortic aneurysms repair

Abstract: Background and Aim: The routine use of cerebrospinal fluid (CSF) drainage in patients undergoing operative repair of thoracoabdominal aneurysms (TAAA) has been associated with decreased rates of spinal cord ischemia. The use of CSF drains is not without consequence, however with complications including subarachnoid hemorrhage, epidural hematoma, meningitis, and, in 1% of cases, death. To date, a decision analysis tool to help clinicians decide when to use and not to use a CSF drain does not exist. In this anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Tam et al 3 utilized a Markov state‐transition cohort model that compared TAAA repair with adjunctive CSF drain insertion to TAAA repair without drain insertion. They demonstrated that the use of CSF drain was associated with improved 5‐year life expectancy and also it reduced the incidence of SCI‐related mortality and morbidity without complication from the CSF drain itself.…”
mentioning
confidence: 99%
“…Tam et al 3 utilized a Markov state‐transition cohort model that compared TAAA repair with adjunctive CSF drain insertion to TAAA repair without drain insertion. They demonstrated that the use of CSF drain was associated with improved 5‐year life expectancy and also it reduced the incidence of SCI‐related mortality and morbidity without complication from the CSF drain itself.…”
mentioning
confidence: 99%